Toward translingual realities in composition : (re)working local language representations and practices - Bou Ayash, Nancy (Utah State University Press, 2019)
"A multi-year ethnographic study of first-year writing programs in Lebanon and Washington State--respectively, a country where English isn't the language of instruction and a state in which English is dominant--to examine the multiple and contradictory manifestations of language ideologies"--Provided by publisher